2019
DOI: 10.1055/s-0039-1700570
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Bone Resection in MAKO Total Knee Robotic-Assisted Surgery

Abstract: Accurate component positioning and planning is vital to prevent malalignment of total knee arthroplasty (TKA) as malalignment is associated with an increased rate of polyethylene wear and revision arthroplasty. The MAKO total knee robotic arm-assisted surgery (Stryker, Kalamazoo, MI) uses a preoperative computed tomography scan of the patient's knee and three-dimensional planning to size and orientate implants prior to bone resection. The aim of this study was to determine the accuracy of the MAKO Total Knee s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 10 publications
7
87
0
1
Order By: Relevance
“…The accuracy of the proposed method is promising with ≤ 1 mm deviation to a 3D scan. These error Table 3 Radiographic measurements values are within clinical acceptance and get close to the threshold value (1 mm) found in robotic-assisted TKA studies [31]. The ICC shows a good and very good correlation for the radiographic measurement between all examiners.…”
Section: Discussionsupporting
confidence: 81%
“…The accuracy of the proposed method is promising with ≤ 1 mm deviation to a 3D scan. These error Table 3 Radiographic measurements values are within clinical acceptance and get close to the threshold value (1 mm) found in robotic-assisted TKA studies [31]. The ICC shows a good and very good correlation for the radiographic measurement between all examiners.…”
Section: Discussionsupporting
confidence: 81%
“…Sires et al. showed that MAKO robotic‐assisted TKA system could improve bone resection accuracy 30 . Recently, Shaw et al 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Sires et al. showed that the MAKO TKA robotic‐assisted system can enhance bone resection precision and component positioning accuracy 36 . In a cadaveric study, Seidenstein et al.…”
Section: Discussionmentioning
confidence: 99%